2022
DOI: 10.1186/s13018-022-02989-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146a expression profiles in osteoarthritis in different tissue sources: a meta-analysis of observational studies

Abstract: Background MiR-146a has been widely studied in the pathogenesis of osteoarthritis (OA); however, the results are still controversial. Objective This meta-analysis analyzes the expression profile of miR-146a in various tissues of OA patients. Methods Public databases were searched for appropriate studies published up to September 1, 2021. A case–control study comparing the OA population and a non-OA hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…miR-146a is one of the most extensively studied miRNAs in relation to OA and inflammation. It has been found to have increased expression in cartilage of OA joints compared to controls in a number of previous studies in human patients (41,(66)(67)(68)(69), and has therefore been suggested as a biomarker of OA. Bioinformatics analysis has demonstrated that miR-146a targets 159 proteins (67), including inflammatory inducers in the nuclear factor kappa B pathway and IL-1β, and factors involved in apoptosis or autophagy (67), which might have been ongoing at the time our horses were euthanized (day 70 after OA-induction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-146a is one of the most extensively studied miRNAs in relation to OA and inflammation. It has been found to have increased expression in cartilage of OA joints compared to controls in a number of previous studies in human patients (41,(66)(67)(68)(69), and has therefore been suggested as a biomarker of OA. Bioinformatics analysis has demonstrated that miR-146a targets 159 proteins (67), including inflammatory inducers in the nuclear factor kappa B pathway and IL-1β, and factors involved in apoptosis or autophagy (67), which might have been ongoing at the time our horses were euthanized (day 70 after OA-induction).…”
Section: Discussionmentioning
confidence: 99%
“…Three miRNAs were upregulated in cartilage from untreated OA joints compared to control joints (miR-146A; miR-150; miR-409-3p). Both miR-146a (36,41,(66)(67)(68)(69) and miR-150 (70,71) are known to be related to OA, whereas miR-409-3p (72, 73) has been described to be involved in regulation of inflammation, which is a prominent part of the OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that miR-146a is a negative regulator of innate immune response [ 75 ], and is associated with inflammatory immune responses (e.g. systemic lupus erythematosus [ 76 ], osteoarthritis [ 77 ], rheumatoid arthritis [ 78 ]), tumors (e.g. colorectal cancer [ 79 ], breast cancer [ 80 ], gastric cancer [ 81 ], lung cancer [ 82 ]), angiogenesis [ 83 , 84 ], apoptosis [ 85 ], and autophagy [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-34a has been known to be implicated in activating apoptosis signaling, limiting cell proliferation, and modulating redox balance in human OA chondrocytes and synovial fibroblasts [ 28 , 29 , 43 , 44 , 45 ]. In addition, miR-146a, traditionally identified as a regulator of inflammation, has been recently recognized as an activator of apoptosis and oxidative stress by its direct effect on SMAD4 and NRF2 transcriptional factors, in OA cells [ 28 , 29 , 46 ]. Similarly, miR-181a activates apoptosis and oxidative stress by targeting the anti-apoptotic marker BCL2 and modulating the oxidant/antioxidant system in different cell types [ 28 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%